Strategi Guru Pendidikan Agama Islam Menerapkan Problem Based Learning dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik di SMA Pembangunan V Yapis Waena - Syifaaul Hasanah; Muhammad Taslim; Sigit Purwaka (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Education plays an important role in shaping the quality of human resources, particularly in developing students' critical thinking skills. In the learning process at school, teachers not only act as providers of information but also as facilitators who are able to create active, creative, and participatory learning environments. However, in practice, the learning process is still often dominated by one-way lecture methods, which tend to make students passive and less involved in the learning process. This condition affects the development of students’ critical thinking skills. Therefore, learning strategies that actively involve students are needed, one of which is through the implementation of Problem Based Learning (PBL).This study aims to analyze the strategies used by Islamic Religious Education teachers in implementing Problem Based Learning and its impact on students’ critical thinking skills at SMA Pembangunan V YAPIS Waena. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation, while data analysis used the Miles and Huberman model which includes data reduction, data display, and conclusion drawing.The results of the study indicate that the implementation of Problem Based Learning is carried out through several stages, including presenting problems related to daily life, group discussions, problem analysis, and the presentation of discussion results by students. The implementation of this learning model increases students’ activeness in the learning process and encourages the development of critical thinking skills, such as identifying problems, analyzing information, expressing opinions, and drawing logical conclusions. Therefore, Problem Based Learning can be considered an effective learning strategy for improving students’ critical thinking skills in Islamic Religious Education learning.